2016
DOI: 10.3109/00016489.2016.1159328
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of balloon dilation eustachian tuboplasty surgery in adult otitis media with effusion

Abstract: None of the involved patients complained of problems or complications during the post-operative period, or with absence of pain and bleeding after the operation. Prominent post-operative improvement was observed in tympanic membrane and otoscopic appearance. In addition, cure rates after 3 months and 6 months post-operatively were gradually increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…Three subgroups used dichotomous data (relative risk [RR]) and one continuous data (mean score and standard deviation [SD]). Two studies in which these subgroups were mentioned had to be excluded due to the absence of data before the ETBD procedure …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three subgroups used dichotomous data (relative risk [RR]) and one continuous data (mean score and standard deviation [SD]). Two studies in which these subgroups were mentioned had to be excluded due to the absence of data before the ETBD procedure …”
Section: Resultsmentioning
confidence: 99%
“…In order to assess potential dehiscence of the bony wall of the internal carotid artery or anomalies of the tuba auditiva, a preoperative (high‐resolution) CT scan of the temporal bone was performed in nine studies and a digital volume tomography in one . The remaining five studies refrained from imaging …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that the etiology may be related to an immature immune system, viral infection, changes in the mechanism of neuroinflammation, poor vaporization of mastoid, or poor function of the eustachian tube, etc. [16]. Among the various causes of eustachian tube dysfunction, the LPRD has gradually attracted attention.…”
Section: Discussionmentioning
confidence: 99%